PERBANDINGAN TOTAL MIKROBA DAN RESPIRASI TANAH PADA LAHAN APLIKASI DAN TANPA APLIKASI LIMBAH CAIR PABRIK KELAPA SAWIT SERTA KORELASINYA - Fitriana, Dewi; Kusuma, Satria E Kusuma; Sakiah, Sakiah; Gunawan, Hari; O Y sitompul, Inggrid (Jurnal Pertanian, 2022)
Oil palm initially produced Crude Palm Oil and Palm Kernel Oil as the main products of fresh fruit bunches, besides that currently the Indonesian palm oil industry utilizes the rest of the processing of fresh fruit bunches is waste as a soil enhancer. This study aims to determine the comparison of the total soil microbes, soil respiration, and the correlation between the two on the application. The research design used was a factorial randomized block design consisting of 2 factors. Factor I is the LCPKS application and factor II is the depth of soil sampling in the oil palm area. Parameters observed were total microbial and soil respiration. The results of observations are arranged in a variance table, if they are significantly different at the 5% level, then it is continued with the DMRT. The relationship between total microbes and soil respiration was analyzed by linear regression. The results showed that the total microbes were significantly different in the application land and without the POME application, the total microbes in the POME application area were higher than in the land without the application. but in the treatment of differences in soil depth there was no significant difference. The total microbial is positively correlated with soil respiration, the greater the total microbial, the higher the soil respiration.